ESG PERFORMANCE AND FIRM VALUE: THE MODERATING ROLE OF OWNERSHIP CONCENTRATION - Taufik; M. Arief Noer Wibowo; Sulastri; Yuliani; Isni Andriana; Afriyadi Cahyadi (CV. Radja Publika, 2026)
The purpose of this study is to analyze how ESG Performance influences firm value and whether ownership concentration moderates the relationship between ESG performance and firm value. The population used is 128 companies in three ASEAN countries (Indonesia, Malaysia, and Thailand) from 2021–2024. A sample of 85 companies was selected using purposive sampling. The results of the study show that ESG performance has a positive effect on firm value and that ownership concentration moderates the relationship between ESG performance and firm value. For further research, it is recommended to add research period and other independent variables inluencing firm value.